The Impact of Laser Thermal Effect on Histological Evaluation of Oral Soft Tissue Biopsy: Systematic Review - Gianluca Tenore; Ahmed Mohsen; Alessandro Nuvoli; Gaspare Palaia; Federica Rocchetti; Cira Rosaria Tiziana Di Gioia; Andrea Cicconetti; Umberto Romeo; Alessandro Del Vecchio (MDPI AG, 2023)
The aim of the study is to review the literature to observe studies that evaluate the extent of the thermal effect of different laser wavelengths on the histological evaluation of oral soft tissue biopsies. An electronic search for published studies was performed on the PubMed and Scopus databases between July 2020 and November 2022. After the selection process, all the included studies were subjected to quality assessment and data extraction processes. A total of 28 studies met the eligibility criteria. The most studied laser was the carbon dioxide (CO2) laser, followed by the diode laser 940 nm-980 nm. Six studies were focused on each of the Erbium-doped Yttrium Aluminium Garnet (Er:YAG), Neodymium-doped Yttrium Aluminum Garnet (Nd:YAG) lasers, and diode lasers of 808 nm and 445 nm. Three studies were for the Potassium Titanyl Phosphate (KTP) laser, and four studies were for the Erbium, Chromium-doped Yttrium, Scandium, Gallium, and Garnet (Er,Cr:YSGG) laser. The quality and bias assessment revealed that almost all the animal studies were at a low risk of bias (RoB) in the considered domains of the used assessment tool except the allocation concealment domain in the selection bias and the blinding domain in the performance bias, where these domains were awarded an unclear or high score in almost all the included animal studies. For clinical studies, the range of the total RoB score in the comparative studies was 14 to 23, while in the non-comparative studies, it was 11 to 15. Almost all the studies concluded that the thermal effect of different laser wavelengths did not hinder the histological diagnosis. This literature review showed some observations. The thermal effect occurred with different wavelengths and parameters and what should be done is to minimize it by better adjusting the laser parameters. The extension of margins during the collection of laser oral biopsies and the use of laser only in non-suspicious lesions are recommended because of the difficulty of the histopathologist to assess the extension and grade of dysplasia at the surgical margins. The comparison of the thermal effect between different studies was impossible due to the presence of methodological heterogeneity.